Interactome Analysis of Bag-1 Isoforms Reveals Novel Interaction Partners in Endoplasmic Reticulum-Associated Degradation - Can, Nisan Denizce; Baştürk, Ezgi; Kızılboğa, Tuğba; Akçay, İzzet Mehmet; Dingiloğlu, Baran; Tatlı, Özge; Acar, Sevilay; KILBAŞ, PELİN ÖZFİLİZ; Elbeyli, Efe; Muratcioglu, Serena; Jannuzzi, Ayşe Tarbin; Gürsoy, Attila; et al. (Public Library Science, 2021)
Bag-1 is a multifunctional protein that regulates Hsp70 chaperone activity, apoptosis, and proliferation. The three major Bag-1 isoforms have different subcellular localizations and partly non-overlapping functions. To identify the detailed interaction network of each isoform, we utilized mass spectrometry-based proteomics and found that interactomes of Bag-1 isoforms contained many common proteins, with variations in their abundances. Bag-1 interactomes were enriched with proteins involved in protein processing and degradation pathways. Novel interaction partners included VCP/p97; a transitional ER ATPase, Rad23B; a shuttling factor for ubiquitinated proteins, proteasome components, and ER-resident proteins, suggesting a role for Bag-1 also in ER-associated protein degradation (ERAD). Bag-1 pull-down from cells and tissues from breast cancer patients validated these interactions and showed cancer-related prominence. Using in silico predictions we detected hotspot residues of Bag-1. Mutations of these residues caused loss of binding to protein quality control elements and impaired proteasomal activity in MCF-7 cells. Following CD147 glycosylation pattern, we showed that Bag-1 downregulated VCP/p97-dependent ERAD. Overall, our data extends the interaction map of Bag-1, and broadens its role in protein homeostasis. Targeting the interaction surfaces revealed in this study might be an effective strategy in the treatment of cancer.
Keywords: Protein-Protein Interactions